PERANCANGAN APLIKASI WEB UNTUK DETEKSI PENYAKIT PARU-PARU DENGAN INFERENCE FORWARD MENGGUNAKAN METODE DEMPSTER SHAFER - Abdiansyah Putra Tanjung (CV. Multi Kreasi Media, 2023)
The lungs are one of the vital organs for human life, especially functioning as a respiratory organ. Many people suffer from lung disease, and the diagnosis is late so that it reaches a chronic stage and is difficult to treat, not a few even have to lose their lives, because people with lung disease must routinely consult with health experts (pulmonary disease specialists). , regarding the disease, as well as the symptoms that are felt. The basic principle is driven by disease information that is carried out using a Web application by requesting requests from users. The request will be processed in the system, then the results will be sent again to the user by displaying it on the web application screen. This system was built to be able to help people who don't understand lung disease in detecting lung disease experienced by these patients without having to go to an expert. These increasingly rapid technological advances also have an effect on the development of current web applications, so that the use of web applications is increasingly widely known. This development is very helpful in presenting information quickly and efficiently with internet access through the web application. By designing a web application using the Dempster Shafer method, it is possible to determine the proportion of lung disease in patients. The percentage of the disease can make it easier for doctors or doctors to treat people with lung disease.